“Bit-Bit” Sebagai Bentuk Perlawanan Dan Do’a Terhadap Eksploitasi Hutan Di Kepulauan Mentawai - Muttakin, Achmad Ghozali Idham; Emri Emri; Stevenson, Yan; Metro, Wardi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The dance work BIT-BIT was inspired by the social phenomenon of forest exploitation currently occurring in the Mentawai Islands. This work embodies resistance and prayer against forest exploitation, which impacts the lives and culture of the Mentawai people. The artist interpreted this idea in group choreography, using eight male and female dancers to represent the artist's concerns about forest exploitation. This work was performed on the Arena stage of the Boestanoel Arifin Adam Auditorium, Indonesian Institute of the Arts, Padangpanjang. The work is divided into three parts. In the first part, the artist interprets the chanting of Urai and the property of Jejeneng to gain strength from ancestral spirits to ward off evil spirits. In the second part, the artist interprets foot stomping as a form of resistance against forest exploitation. In the third part, the artist interprets Urai as a symbol of prayer and hope to voice the Mentawai people's concerns about forest exploitation.